Engineering Judgment of Children Bone Fracture - A. Alsamhan; M. M. ELSingergy; M. M. Zamzam; S. M. Darwish (International Journal of Biomaterials)
Supracondylar humerus fracture (SCHF) is one of the commonest elbow fractures in children. It is common injury for children with age from four to fourteen. In current study, the finite element technique is used to evaluate two techniques, namely, parallel and crossed K-wire fixation for treatment of SCHF, using K-wire fixation.